Characterization method of microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation
By observing high magnification in the characteristic area of the sample, the high fuel consumption structure of UO2 nuclear fuel after irradiation was characterized, and the problem of difficult to observe the multilateralization process of pore nucleation points and grain boundaries in the prior art was solved, and the high The reasons for the formation of fuel consumption structures help understand the failure mechanism of fuel components.
Patent Information
- Application Number
- CN202210906443.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-07-29
AI Technical Summary
The prior art is difficult to observe the high-fuel microstructure of strongly radioactive UO2 nuclear fuel after irradiation, especially the multilateralization process of the nucleation point and grain boundary of the pores, making it difficult to understand the mechanism of fuel element failure.
By finding characteristic areas on the sample, such as cutting edge zone, grinding and falling micro-region on the edge of the fuel core pellet, and grinding complete zone, high magnification observation is performed using field emission scanning electron microscope to characterize the pores formed by fission gas accumulation in the grain boundary The proportion and size of nucleation and the evolutionary state of grain refinement behavior reveal the reasons for the formation of high-fuel consumption structures.
It realizes a clear characterization of the high-fuel consumption structure, reveals the reasons for the formation of the high-fuel consumption structure, helps to understand the failure mechanism of fuel elements, and avoids the problem of destruction of the interface morphology of grain boundaries and fission product enrichment phases in the prior art.
Smart Images

Figure CN115266530B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nuclear fuel cycle and irradiation effect, and in particular to a method for characterizing the high burnup microscopic morphology of highly radioactive UO2 nuclear fuel after irradiation. Background Art
[0002] Rod-shaped fuel elements are a common fuel element configuration in pressurized water reactors, with zirconium alloy cladding material on the outside and UO2 fuel pellets on the inside. When the burnup of the fuel element is further increased (~>50 MWD / tU), the PCI (pellet-cladding mechanical interaction) effect may lead to the problem of fuel element failure. The root cause of the PCI effect comes from the formation of high-burnup structure of the fuel. High-burnup structure refers to the microstructure in which fine recrystallized grains are formed in the fuel after the burnup increases, and fission gas gathers to form pores. Because this structure often appears in the radial periphery of the light water reactor fuel pellet, researchers later used the term "rim zone structure" with technical connotations to describe it. After the high-burnup structure is formed, the fuel pellet will swell significantly, and the risk of fuel element failure will increase. Therefore, a thorough understanding of the formation of high-burnup structure is of great significance for understanding the failure mechanism of fuel elements.
[0003] However, it is still difficult to characterize the high burnup structure of irradiated fuel by scanning electron microscopy, because it is difficult to observe the nucleation point of pores and the polymorphization process of grain boundaries in the ordinary area of the obtained radioactive sample. Therefore, it is necessary to take appropriate methods and measures to solve the above problems in order to obtain the high burnup microstructure of highly radioactive UO2 nuclear fuel after irradiation. Summary of the invention
[0004] The technical problem to be solved by the present invention is that it is currently very difficult to characterize and observe the high burnup microstructure of highly radioactive UO2 nuclear fuel after irradiation. It is difficult to observe the nucleation point of pores and the polymorphization process of grain boundaries in the ordinary area of the sample. In order to solve the above problem, the present invention provides a method for characterizing the high burnup microstructure of highly radioactive UO2 nuclear fuel after irradiation, and uses the characteristic area on the sample to characterize the high burnup morphology of the sample, so as to analyze the evolution and formation process of the high burnup structure and reveal the reasons for the formation of the high burnup structure.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for characterizing the high-burnup microscopic morphology of highly radioactive UO2 nuclear fuel after irradiation, wherein the sample used for characterization is a sample with a high-burnup structure;
[0007] Characterization methods include:
[0008] Find characteristic areas on the sample for morphological characterization and observation, the characteristic areas include the sample cutting edge area, the grinding and shedding micro-area of the fuel pellet edge, and the sample grinding complete area. The sample cutting edge area shows the grain boundary of the fuel phase, and the grinding and shedding micro-area of the fuel pellet edge is formed by the separation of part of the fuel phase of the fuel pellet;
[0009] The proportion and size of pores formed by fission gas accumulation at the grain boundary nucleation were observed in the cutting edge area of the sample;
[0010] Characterize and observe the evolution of grain refinement behavior in the grinding-shedding micro-region at the edge of the fuel pellet;
[0011] Observe the size and distribution of pores in the polished complete area.
[0012] In an optional embodiment, the proportion and size of the pores formed by the fission gas aggregation at the grain boundary nucleation include: the distribution ratio of the pores falling on the grain boundary and inside the grain, and the size of the pores at the grain boundary and the pores inside the grain.
[0013] In an optional embodiment, the evolution state of the high-burnup structure includes a grain boundary polygonization process, and characterizing and observing the grain boundary polygonization process includes: characterizing the morphology and size of fine-grained grains, and the evolution form and advancement mode of the fission product-rich phase.
[0014] In an optional embodiment, field emission scanning electron microscopy is used for characterization.
[0015] In an optional embodiment, the size and distribution of pores are observed in the polished complete area under a field emission scanning electron microscope at a magnification of 10,000 times.
[0016] In an optional embodiment, the proportion and size of pores formed by fission gas aggregation and nucleation at grain boundaries are observed under a field emission scanning electron microscope at a magnification of 10,000 times.
[0017] In an optional embodiment, the evolution state of the grain refinement behavior is observed using a field emission scanning electron microscope 20000-300000.
[0018] In an optional embodiment, the cut edge area of the sample presents a fracture morphology and has mechanical stress characteristics, making the grain boundary morphology easy to observe;
[0019] The processing method of the sample cutting edge is: using a precision cutting machine to cut the nuclear fuel assembly into small sections, the precision cutting machine has a cutting accuracy of better than 0.1mm for ceramic materials in a hot chamber, and during the cutting process, the cutting machine is controlled to feed 0.1-0.2mm each time, and the cutting speed is 0.05-0.2m / min.
[0020] In an optional embodiment, the grinding-off micro-region of the fuel pellet edge on the sample is within the range of 0.5 mm to 1 mm of the mechanical stress influence zone close to the cutting edge.
[0021] In an optional embodiment, the processing of the sample further includes polishing and coating after cutting, inlaying and grinding;
[0022] The grinding conditions are as follows: after epoxy resin cold mounting, grinding was performed for 5 min each under three conditions: 200-mesh grinding disc pressure 30N, 600-mesh sandpaper pressure 30N, and 1200-mesh sandpaper pressure 30N;
[0023] The polishing conditions were as follows: grinding for 5 min each at 9μ diamond suspension pressure 15N, 3μ diamond suspension pressure 15N, and 1μ diamond suspension pressure 15N;
[0024] The coating condition is vacuum degree less than 10 -2 Spray-deposit gold film at Pa for 15 seconds.
[0025] In an optional embodiment, the sample processing process is all carried out in a hot chamber, the processed samples are transported to the electron microscope room by shielded transportation, and the sample loading is completed in a shielded glove box.
[0026] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0027] The embodiment of the present invention provides a method for characterizing the high burnup microstructure of highly radioactive UO2 nuclear fuel after irradiation. During the cutting process, a cutting edge area of the sample is formed to present the grain boundary of the fuel phase, so that the grain boundary of the fuel core block is easy to observe; during the grinding process, the cutting stress influence area causes part of the fuel phase of the fuel core block to fall off, so that the multi-sided morphology of the grain boundary of the high burnup structure is fully presented. Based on this, the present invention uses the characteristic area to characterize the high burnup morphology of the sample, and can clearly obtain the high burnup microstructure morphology, so as to analyze the evolution and formation process of the high burnup structure and reveal the reasons for the formation of the high burnup structure, which is of great significance for understanding the failure mechanism of the fuel element. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0029] Figure 1 A schematic diagram of the high burnup structure of a UO2 fuel element obtained by using a method for characterizing the high burnup microscopic morphology of highly radioactive UO2 nuclear fuel after irradiation proposed in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0031] At present, the high burnup microstructure of highly radioactive UO2 nuclear fuel is characterized by scanning electron microscopy. The samples are prepared by conventional grinding, polishing and observation of the central area of the sample. This sample preparation method causes the morphology of grain boundaries and fission product-rich phase interfaces to be destroyed, and it is difficult to observe the nucleation points of pores and the polynomialization process of grain boundaries in ordinary areas of the samples prepared in this way. Therefore, it is impossible to obtain the high burnup microstructure of highly radioactive UO2 nuclear fuel after irradiation from multiple angles and in a complete manner.
[0032] In order to solve the above problems, an embodiment of the present invention provides a method for characterizing the high burnup microscopic morphology of highly radioactive UO2 nuclear fuel after irradiation. The sample used for characterization is a sample with a high burnup structure and a burnup of >50 MWD / tU.
[0033] Specific characterization methods include:
[0034] Cutting the nuclear fuel assembly into small sections, and processing the small sections, wherein the processing includes grinding, so that characteristic areas are formed on the sample, and the characteristic areas include the sample cutting edge area, the grinding and shedding micro area of the fuel pellet edge, and the sample grinding complete area;
[0035] The above-mentioned characteristic areas are sought during characterization. The proportion and size of pores formed by fission gas accumulation at the grain boundary nucleation are observed through the cutting edge area of the sample. The evolution state of the high-burnup structure, including the grain boundary polygonization process, is observed through the grinding and shedding micro-area at the edge of the fuel core block. The size and distribution of the pores are observed through the grinding complete area.
[0036] Since the cutting edge area of the sample is formed during the cutting process, the grain boundary of the fuel phase is presented, making it easy to observe the grain boundary of the fuel pellet; since part of the fuel phase of the fuel pellet falls off during the grinding process, the multi-sided morphology of the grain boundary of the high-burnup structure is fully presented. Compared with observing the ordinary area in the existing characterization process, the patent of this invention uses the characteristic area to characterize the high-burnup morphology of the sample, and can clearly obtain the high-burnup microstructure morphology to analyze the evolution and formation process of the high-burnup structure and reveal the reasons for the formation of the high-burnup structure.
[0037] Furthermore, the proportion and size of the pores formed by the accumulation of fission gas at the grain boundary nucleation include: the distribution ratio of the pores falling on the grain boundary and inside the grain, and the size of the pores at the grain boundary and the pores inside the grain.
[0038] Furthermore, the evolution state of the high-burnup structure includes a grain boundary polygonization process, and characterization and observation of the grain boundary polygonization process includes: characterization of the morphology and size of recrystallized grains, the evolution form and advancement mode of the fission product-rich phase, and the advancement mode includes the advancement form of the fission product-rich phase from the inside of the pores toward the inside of the grains, and the advancement form of the fission product-rich phase from the original grain boundaries toward the inside of the grains.
[0039] Furthermore, field emission scanning electron microscopy was used for characterization to obtain high-definition morphology images.
[0040] Furthermore, the size and distribution of pores were observed in the grinding complete area under a field emission scanning electron microscope at 10,000 times; the proportion and size of pores formed by fission gas accumulation at the grain boundary nucleation were observed under a field emission scanning electron microscope at 10,000 times; the evolution state of grain refinement behavior, including the morphology and size of recrystallized grains, the evolution morphology and advancement mode of fission product enriched phase, was observed under a field emission scanning electron microscope at 20,000-300,000. A good morphological feature map can be obtained at the corresponding magnification.
[0041] Furthermore, the cut edge area of the sample presents a fracture morphology and has mechanical stress characteristics, making the grain boundary morphology easy to observe.
[0042] The processing method of the cutting edge of the sample is: using a precision cutting machine to cut the nuclear fuel assembly into small sections. The precision cutting machine has a cutting accuracy of better than 0.1mm for ceramic materials in a hot chamber. During the cutting process, a relatively fast cutting rate is controlled, that is, the feed amount is 0.1-0.2mm each time, and the cutting speed is 0.05-0.2m / min. Under a large cutting stress, it can not only avoid the cutting and crushing of nuclear fuel and the generation of strong release debris, but also make the grain boundaries appear and the grinding and shedding of micro-areas.
[0043] Since the fuel element contains both fuel pellets and alloy cladding material, currently when preparing samples, if one wants to make the grain boundaries of the fuel phase visible, the method used is etching, in which the fuel pellets are etched. However, this method is difficult to make the grain boundaries of the fuel phase visible because the etchant preferentially corrodes the more active metal cladding material, and the generated corrosion products are difficult to remove cleanly in the hot chamber. In the embodiment of the present invention, the cutting mechanical stress is controlled to make the grain boundaries of the fuel phase visible for easy observation.
[0044] Furthermore, the micro-region where the fuel core block edge on the sample is ground and detached is within the range of 0.5mm-1mm close to the mechanical stress influence zone of the cutting edge. Due to the grain refinement behavior or the precipitation of the fission product-rich phase, the cutting stress within this range easily causes the cracks in the fine grain area to initiate and expand, and then fall off under the action of grinding.
[0045] The processing process of the grinding-off micro-region of the edge of the fuel pellet on the sample is: cutting the nuclear fuel assembly, inlaying and grinding, and the stress intensity is controlled to be 30N during the grinding process.
[0046] Since it is difficult to observe a complete high-burnup structure in most areas of the fuel pellets in samples prepared by existing methods, the stress in the grinding process is controlled in the embodiments of the present invention so that the fuel pellets fall off through cleavage fracture, and the grain boundary polygonal morphology of the high-burnup structure is fully presented.
[0047] Furthermore, the processing of the specimens also includes polishing and coating after cutting, mounting and grinding;
[0048] Furthermore, the grinding conditions are as follows: after epoxy resin cold embedding, grinding is performed for 5 minutes each under three conditions: 200-mesh grinding disc pressure 30N, 600-mesh sandpaper pressure 30N, and 1200-mesh sandpaper pressure 30N.
[0049] Furthermore, the polishing conditions are 9μ diamond suspension pressure 15N, 3μ diamond suspension pressure 15N, and 1μ diamond suspension pressure 15N, each for 5 minutes.
[0050] Furthermore, the coating condition is a vacuum degree less than 10 -2 The gold film was sprayed for 15 seconds at 400 Pa. Furthermore, the sample processing process was carried out in the hot room, and the processed samples were transported to the electron microscope room by shielding transportation, and the sample loading was completed in the shielding glove box.
[0051] Since the irradiated fuel sample is highly radioactive, it is easy to threaten the health of the experimenters. At the same time, high-precision characterization equipment may face the problem of radiation damage and failure. In addition, a large number of volatile nuclides released from the irradiated fuel sample may contaminate the experimental environment. In order to solve the irradiation problem, in the embodiment of the present invention, shielding measures are taken during the sample processing, sample transportation and characterization test in the hot chamber to reduce the risk of irradiation.
[0052] The following is an explanation through specific examples.
[0053] Embodiment 1:
[0054] A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation comprises the following steps:
[0055] 1. Sample processing: Use a precision cutting machine to cut the nuclear fuel assembly into small sections. The cutting process is 0.2mm per cutting amount, 0.2m / min cutting speed, and moderate sample size (about 1cm*0.8cm*0.5cm. If it is too large, the dosage will be too high, and if it is too small, it will affect the clamping and prevent the remote operation of the manipulator in the hot chamber). Then embed it, and control the stress intensity for grinding, polishing and coating. After the epoxy resin cold embedding is left to stand overnight, it is ground for 5 minutes under three conditions: 200 mesh grinding disc pressure 30N, 600 mesh sandpaper pressure 30N, and 1200 mesh sandpaper pressure 30N. The polishing conditions are 9μ diamond suspension pressure 15N, 3μ diamond suspension pressure 15N, and 1μ diamond suspension pressure 15N. The observation side of the sample faces up and the vacuum degree is less than 10 -2 The gold film was sprayed at 4000 ℃ and 10000 ℃ for 15 seconds to reduce the volatilization of volatile nuclides and the formation of radioactive aerosols; the above processes were all carried out in a hot room.
[0056] 2. Sample transportation: Use a sealed lead barrel and a transfer cart to transport the sample to the electron microscope room.
[0057] 3. Sample loading: Place the sample on the SEM sample stage in a shielded glove box. Under the protection of shielded gloves, the operator uses copper conductive glue to directly connect the sample observation surface and the sample holder. Turn on the negative pressure fan in the laboratory room to reduce the volatilization of the sample radionuclides.
[0058] 4. Characterization observation:
[0059] a. First observe at a low magnification of 500 times, find the characteristic area, and zoom in to observe:
[0060] b. Observe the size and distribution of pores in the complete grinding area, with a magnification of 10,000 times, and count the size of the pores.
[0061] c. Observe the grain boundary polygonization process in the grinding and shedding micro-area with a magnification of 20,000-300,000 times to characterize the morphology and size of the recrystallized grains, the evolution form and advancement mode of the fission product-rich phase; including the size of the recrystallized grains inside the pores, the advancement form of the fission product-rich phase from the inside of the pores to the inside of the grains, and the advancement form of the fission product-rich phase from the original grain boundaries to the inside of the grains.
[0062] d. In the cut edge area of the fuel core, magnify 10,000 times and observe the distribution ratio of the pores at the grain boundaries and inside the grains, and observe the size of the pores at the grain boundaries and inside the grains.
[0063] The high burnup structure of the grain boundary evolution behavior of the UO2 fuel element in the detached area is obtained by using the characterization technology of the present invention. Figure 1 As shown by Figure 1 It can be seen that under the current burnup, in the region near the original grain boundary in the fuel, the refined grains of the fission product-enriched phase have begun to form. There is no obvious pore morphology in this region. The surface grain boundary polygonization can be formed by nucleation and growth at the grain boundary without relying on micron-sized pores. The fission product-enriched phase is first formed at the grain boundary, and then advances into the crystal in a parallel form, which is related to the fission product migration and diffusion dynamics and the stress field distribution of the precipitate. Its high burnup structural evolution state is clear and complete.
[0064] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation, characterized in that: The specimens used for characterization are those with high burnup structure; Characterization methods include: Finding characteristic areas on the prepared sample for morphological characterization and observation, the characteristic areas include the sample cutting edge area, the grinding and shedding micro-area of the fuel pellet edge, and the sample grinding complete area, the sample cutting edge area presents the grain boundary of the fuel phase, and the grinding and shedding micro-area of the fuel pellet edge is formed by the separation of part of the fuel phase of the fuel pellet; The proportion and size of pores formed by fission gas accumulation at the grain boundary nucleation were observed in the cutting edge area of the sample; Characterize and observe the evolution of grain refinement behavior in the grinding-shedding micro-region at the edge of the fuel pellet; Observe the size and distribution of pores in the complete grinding area; Field emission scanning electron microscopy was used for characterization; The sample processing also includes cutting, mounting, grinding, polishing and coating.
2. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The proportion and size of the pores formed by the accumulation of fission gas at the grain boundary nucleation include: the distribution ratio of the pores falling on the grain boundary and inside the grain, and the size of the pores at the grain boundary and the pores inside the grain.
3. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The evolution state of the high-burnup structure includes the grain boundary polygonization process. The characterization and observation of the grain boundary polygonization process includes: characterizing the morphology and size of fine-grained grains, the evolution form and advancement mode of the fission product-rich phase.
4. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The size and distribution of pores were observed in the polished complete area under a field emission scanning electron microscope at 10,000 times magnification.
5. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The proportion and size of pores formed by fission gas accumulation at grain boundaries were observed under a field emission scanning electron microscope at 10,000 times magnification.
6. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The evolution state of grain refinement behavior was observed under a field emission scanning electron microscope at a magnification of 20,000-300,000 times.
7. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The cutting edge area of the sample presents a fracture morphology and has mechanical stress, making the grain boundary morphology easy to observe; The processing method of the sample cutting edge is: using a precision cutting machine to cut the nuclear fuel assembly into small sections, the precision cutting machine has a cutting accuracy of better than 0.1mm for ceramic materials in a hot chamber, and during the cutting process, the cutting machine is controlled to feed 0.1-0.2mm each time, and the cutting speed is 0.05-0.2m / min.
8. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The grinding-off micro-region of the fuel pellet edge on the sample is within the range of 0.5 mm to 1 mm of the mechanical stress influence zone close to the cutting edge.
9. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The grinding conditions are as follows: after cold embedding with epoxy resin, grinding is performed for 5 minutes under three conditions: 200-mesh grinding disc pressure 30N, 600-mesh sandpaper pressure 30N, and 1200-mesh sandpaper pressure 30N; The polishing conditions are: grinding for 5 minutes each under three conditions: 9μ diamond suspension pressure 15N, 3μ diamond suspension pressure 15N, and 1μ diamond suspension pressure 15N; The coating condition is that the vacuum degree is less than 10 -2 Spray-deposit gold film at Pa for 15 seconds.
10. A method for characterizing the microscopic morphology of highly radioactive UO2 nuclear fuel with high burnup after irradiation as claimed in claim 1, characterized in that: The sample processing process is carried out in a hot chamber. The processed samples are transported to the electron microscope room by shielded transfer, and the sample loading is completed in a shielded glove box.